Poverty, inequality, and social policies in Peru: as poor as it gets - Yamada Fukusaki, Gustavo (2012)
This paper analyzes trends in poverty, income inequality and social policies in Peru in the last twenty years. Our objective is to explain what lies behind the generalized perception and complain by Peruvians that welfare and living standards have not got any better in at least two generations. We find problems in several fronts: lower expenditure than the average in the region, which could explain restrictions in coverage and quality of services, but also problems related to targeting, delivery of services, and overlapping, and deficient design and choice of effective programs. We also discuss why is that social policies have failed to deliver crucial assets for short, and specially, long term poverty and inequality alleviation in Peru, and present some guidelines to improve social policy design and implementation in Peru given past lessons, with special emphasis on the Millennium Development Goals (MDG) framework as a tool for policy planning, design, and costing.